(3EbJUGOjGJ UQa GdfbhO h GdYedGJs - (3GdWGgQ(B, (3bGfIs ((3GdLRGFQ(B:s (3OGQ GdNdOhfjI(B,s, 2009)
(3eaGgje CSGSjI dSYQ GdUQa h JMOjOg , CYVGA Shb GdUQa h GdYedjGJ ajg G, SYQ GdUQa gOa NGU ddSjGSI GdfbOjI , JONd GdHfc GdeQcRj aj Shb GdUQa , SjGSI GdJYhje h CSHGH YOe GdGSJbQGQ , JcGdja YOe GdGSJbQGQG , eaghe GdUQa h eTQhYjJg aj GdGbJUGO GdGSdGej , CQcGf YbO GdUQa h TQhWg aj GdGbJUGO GdGSdGej , GMcGe YbO GdUQa aj GdGbJUGO GdGSdGej , GdUQa ceG JLQHg GdeUGQa GdGSdGejI , eJWdHGJ JWHjb GdGbJUGO GdGSdGej (B.s
(3eQGLY U(B.89 ((3EbJfGAGJ (B2014 3(3f(B)s
Keywords: (3CSYGQ UQa GdYedGJ GdCLfHjIs; (3GdEbJUGO GdGSdGejs